Writing gender, writing nation : women's fiction in post-independence India - Arora, Bharti (New York : Routledge, 2020)
"This book explores the gendered contexts of the Indian nation through a rigorous analysis of selected women's fiction ranging from diverse linguistic, regional, geographical, caste, class and regional contexts. Indian women's writing across languages, texts, and contexts constitutes a unique narrative of the post-independence nation. This volume highlights the ways in which women writers negotiate the patriarchal biases embedded in the epistemological and institutional structures of the post-independence nation state. It discusses works of famous Indian authors like Amrita Pritam, Jyotirmoyee Devi, Mannu Bhandari, Mahasweta Devi, Mridula Garg, Nayantara Sahgal, Indira Goswami, Alka Saraogi to name a few, and facilitates a pan-Indian understanding of the concerns taken up by these women writers. In doing so, it shows how ideas travel across regions and contribute towards building a thematic critique of the oppressive structures that breed the unequal relations between margins and the centre. The volume will be of interest to scholars and researchers of gender studies, women's studies, South Asian literature, political sociology and political studies"--
Revision of author's thesis (doctoral)--Jamia Millia Islamia (India), 2018, titled Writing gender, writing nation : a critical study of select women's fiction in post-independence India.
Keywords: Indic fiction -- Women authors -- History and criticism; Indic fiction -- 20th century -- History and criticism; Indic fiction -- 21st century -- History and criticism; Women and literature -- India -- History -- 20th century; Women and literature -- India -- History -- 21st century